Duplication of 8q24 in Chronic Lymphocytic Leukemia: Cytogenetic and Molecular Biologic Analysis of MYC Aberrations - Ondroušková, Eva; Bohúnová, Michaela; Závacká, Kristýna; Čech, Patrik; Šmuhařová, Petra; Boudný, Miroslav; Oršulová, Martina; Panovská, Anna; Radová, Lenka; Doubek, Michael; Plevová, Karla; Jarošová, Marie (Frontiers in Oncology, 2022)
Chronic lymphocytic leukemia (CLL) with cytogenetics findings, such as complex karyotype and deletions of TP53 or ATM, is associated with adverse clinical outcomes. Additional chromosomal abnormalities further stratify patients into groups with diverse prognoses. Gain of 8q24 is one of the abnormalities considered as prognostically unfavorable. In our study, we performed a FISH analysis in an initial cohort of 303 consecutive CLL patients and determined the frequency of +8q to be 6.3 %. Our analysis confirmed the association with TP53/ATM aberrations and CK, as the frequency of +8q reached 26.7 % in an extended delTP53/ATM+CK cohort. M-FISH analysis enabled the identification of partner chromosomes where the segment of the duplicated 8q arm was localized. More detailed mapping of the gained 8q region using the M-BAND method determined the smallest amplified region 8q23-8qter. We observed significantly shorter overall survival (OS; 9.0 years in +8q-positive vs. 10.6 years in +8q-negative; p=0.02) and detected slightly higher MYC mRNA/protein levels in +8q-positive vs. +8q-negative patients.